The Sleeping Beauty killer - Clark, Mary Higgins; Burke, Alafair (Clark, Mary Higgins. Under suspicion novel, 2016)
"Television producer Laurie Moran puts everything on the line to help a woman she thinks was wrongfully convicted of murder"--